2022
DOI: 10.1111/sdi.13082
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal calprotectin level in peritoneal dialysis patients

Abstract: Background: Calprotectin is an important molecule in the initiation and progression of the inflammatory process. Systemic and local intraperitoneal inflammation are distinct processes and consequences in peritoneal dialysis (PD). We aimed to evaluate dialysate calprotectin levels and its associations with peritonitis and dialysis adequacy in PD patients.Methods: Forty-four PD patients were included in this prospective study. Calprotectin concentration was evaluated in 24-h peritoneal drainage fluid. Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…The first report to assess peritoneal calprotectin in patients with peritonitis was by Sevik et al (2022) who exhibited that the peritoneal calprotectin increased (44). While the study by Heller et al (2011) showed that urinary calprotectin was 60.7 times higher in intrinsic Acute Kidney Injury (45).…”
Section: Underbjerg Et Al (mentioning
confidence: 99%
“…The first report to assess peritoneal calprotectin in patients with peritonitis was by Sevik et al (2022) who exhibited that the peritoneal calprotectin increased (44). While the study by Heller et al (2011) showed that urinary calprotectin was 60.7 times higher in intrinsic Acute Kidney Injury (45).…”
Section: Underbjerg Et Al (mentioning
confidence: 99%